Geographic availability and accessibility of day care services for people with dementia in Ireland - Tom Pierse; Fiona Keogh; Eamon O'Shea; John Cullinan (BMC, 2020)
Abstract Background Day care is an important service for many people with dementia and their carers. In Ireland, day care services for people with dementia are delivered by a mix of dementia-specific day care centres as well as generic day care centres that cater for people with dementia to various degrees. In this paper we examine the geographic distribution of day care services for people with dementia relative to potential need. Methods Using a national survey of day care centres, we estimate the current availability of day care services for people with dementia in the country. We use geographic information systems (GIS) to map day care provision at regional and sub-regional levels and compare this to the estimated number of people with dementia in local areas. Results There is significant variation across the country in the existing capacity of day care centres to cater for people with dementia. The number of places per 100 persons with dementia in the community varies from 14.2 to 21.3 across Community Health Organisation areas. We also show that 18% of people with dementia do not live within 15kms of their nearest day care centre. Conclusion Currently, day care centres, in many parts of the country, have limited capacity to provide a service for people with dementia who live in their catchment area. As the number of people with dementia increases, investment in day care centres should be targeted to areas where need is greatest. Our GIS approach provides valuable evidence that can help inform decisions on future resource allocation and service provision in relation to day care.